Respuesta :

So, the distance between two points (x1,y1) and (x2,y2) is:

d = sqrt( (x2-x1)^2 + (y2-y)^2 )

Some times is better the square of the distance:

d^2 = (x2-x1)^2 + (y2-y)^2

Now, in your case:

5^2 = (0-2)^2 + ( -6-k)^2 = (-2)^2 + (6+k)^2 = 4 + (6+k)^2

Notice the little thing about (-6-k)^2 = (6+k)^2 (less '-') Finally:

25 = 4 + (6+k)^2 ===> (6+k)^2 = 21,

6+k  = sqrt(21)

Notice we did not expand (6+k)^2! No need this time. But now, the tricky part!

6+k=+sqrt(21) and 6+k=-sqrt(21), because both work (never forget that sqrt come with +/- when looking for solutions!)

k = -6 + sqrt(21) and k=-6-sqrt(21).

Both are valid answers. Some times one is not good because you need the solution be positive (for instance), but here, both are good.


Given the points (2,k) and (0,−6) for which values of k would the distance between the points be  √5 ?

We will find that there are two possible values of k;

k = -5 and k = -7.

We know that the distance between two points (x₁, y₁) and  (x₂, y₂) is given by:

[tex]d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2}[/tex]

Here we have the points (2,k) and (0,−6), then the distance will be given by:

[tex]d = \sqrt{(2 - 0)^2 + (k - (-6))^2} = \sqrt{4 + (k + 6)^2}[/tex]

Now we want to find the value of k such that the distance is equal to √5, then we need to solve:

[tex]\sqrt{5} = \sqrt{4 + (k + 6)^2}[/tex]

removing the square root in both sides we get:

[tex]5 = 4 + (k + 6)^2\\\\5 - 4 = (k + 6)^2\\\\1 = (k + 6)^2[/tex]

Then we can see that (k + 6) = ± 1, solving these two equations (one for each sign) we get:

k + 6 = 1

k = 1 - 6 = -5

and

k + 6 = -1

k = -1 - 6 = -7

Then we found two possible values of k:

k = -5

k = -7

Below you can see the graph of the points A = (2, -5), B = (0, -6) and C = (2, -7)

If you want to learn more about distances, you can read:

https://brainly.com/question/5057237

Ver imagen facundo3141592